2015
DOI: 10.1007/s00586-015-4070-3
|View full text |Cite
|
Sign up to set email alerts
|

A cadaveric study of the cervical nerve roots and spinal segments

Abstract: We anatomically measured the width of cervical nerve roots and spinal segments. The spinal segment of C8 was significantly narrower than some of the roots located in the middle of the cervical spine, and this characteristic continued to the entry of the root in the vertebral foramen, although the difference disappeared at the maximum width point of the root.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Shinomiya et al 17 investigated the width of the spinal segment from C5 to C8 using cadavers and reported that C6 was the widest and C8 the narrowest. Kobayashi et al 18 also confirmed that C8 was the narrowest, and this characteristic continued to the entry of the root in the foramen. Karatas et al 16 measured the widths from C2 to C8 and found that the longest longitudinal length was at C5, whereas the shortest was at C2.…”
Section: Discussionmentioning
confidence: 84%
“…Shinomiya et al 17 investigated the width of the spinal segment from C5 to C8 using cadavers and reported that C6 was the widest and C8 the narrowest. Kobayashi et al 18 also confirmed that C8 was the narrowest, and this characteristic continued to the entry of the root in the foramen. Karatas et al 16 measured the widths from C2 to C8 and found that the longest longitudinal length was at C5, whereas the shortest was at C2.…”
Section: Discussionmentioning
confidence: 84%
“…Shinomiya et al [17] investigated the width of the spinal segment from C5 to C8 using cadavers and reported that C6 was the widest and C8 the narrowest. Kobayashi et al [18] also con rmed that C8 was the narrowest, and this characteristic continued to the entry of the root in the foramen. Karatas et al [16] measured the widths from C2 to C8 and found that the longest longitudinal length was at C5, whereas the shortest was at C2.…”
Section: Discussionmentioning
confidence: 89%
“…; Kobayashi et al. ). This is defined by these authors as the distance measured over the cord between the border fila radicularia of adjacent roots where these fila radicularia leave the cord surface.…”
Section: Discussionmentioning
confidence: 96%